Cubital tunnel syndrome with small occult ganglion: A case report of bike rider. (December 2020) - Kuboi, Takuro; Tajika, Tsuyoshi; Endo, Fumitaka; Hatori, Yuhei; Saida, Ryuta; Chikuda, Hirotaka
Cubital tunnel syndrome, the second-most common peripheral compression neuropathy, is associated with dynamic pressure in the cubital tunnel with the elbow flexion position. Medial elbow ganglion originated from the ulnohumeral joint causing cubital tunnel syndrome has been reported. This report describes the case of a 48-year-old man who developed numbness in his left ring and little finger after prolonged motorbike touring. He gradually showed decreased hand grip strength with medial elbow joint pain. Ultrasonography and magnetic resonance images revealed small occult ganglion at the medial side of elbow joint. Surgical resection of ganglion and ulnar nerve decompression relieved the ulnar neuropathy symptom. Prolonged motorbike riding while maintaining the elbow flexion position might exacerbate the symptom of cubital tunnel syndrome in patients with even a small space-occupying lesion such as the small occult ganglion.